Price and Volatility Spillovers of the Producer Price of Milk between some EU Member States - Jańos Szenderaḱ; Joźsef Popp; Mońika Harangi-Raḱos (German Journal of Agricultural Economics (GJAE), 2019)
The aim of this analysis is to compute the return and volatility spillovers of raw milk prices paid to producers in Germany, Hungary, Italy and Poland with the inclusion of world prices, in the time period between January 2003 and June 2017. This study poses the questions: what is the level of spillovers of the producer price of milk among these Member States? Has the level of spillovers
Keywords: 330